Charles Dickens' Hypnagogia, Dreams, and Creativity - da Mota Gomes, Marleide; Nardi, Antonio E. (Frontiers in Psychology, 2021)
Charles Dickens outlined a variety of manifestations of sleep and its disturbances, which were presumably related to his own and those of family and friends, also expressed in some of his characters. There are many reports of the dream-reality confusion through the anguished young Oliver Twist, the protagonist of the book of the same name. The virtual world of dreams is important for Dickens’ narrative structure, especially in the experiences of Oliver Twist, as well as in the lively, and extensive perceptions with many scenarios of Ebenezer Scrooge, an old miser, from the book Carol Night. Consequently, dreams fulfill the gap between sleep and conscious cognition, and they are oneiric conceptions that are reported in young and old. Furthermore, it seems that Dickens used sleep, usually hypnagogia, perhaps REM lucid dreaming, as a creative work process, as is more easily seen in narcoleptics, besides he expressed these phenomena in his characters. The present study refers to some reports of Dickens’ characters through the current view of sleep and dreams neurobiology.